Formulation of evidence-based messages to promote the use of physical activity to prevent and manage Alzheimer's disease. (December 2017) - Ginis, Kathleen; Heisz, Jennifer; Spence, John; Clark, Ilana; Antflick, Jordan; Ardern, Chris; Costas-Bradstreet, Christa; Duggan, Mary; Hicks, Audrey; Latimer-Cheung, Amy; Middleton, Laura; Nylen, Kirk; et al.
Abstract Background The impending public health impact of Alzheimer's disease is tremendous. Physical activity is a promising intervention for preventing and managing Alzheimer's disease. However, there is a lack of evidence-based public health messaging to support this position. This paper describes the application of the Appraisal of Guidelines Research and Evaluation II (AGREE-II) principles to formulate an evidence-based message to promote physical activity for the purposes of preventing and managing Alzheimer's disease. Methods A messaging statement was developed using the AGREE-II instrument as guidance. Methods included (a) conducting a systematic review of reviews summarizing research on physical activity to prevent and manage Alzheimer's disease, and (b) engaging stakeholders to deliberate the evidence and formulate the messaging statement. Results The evidence base consisted of seven systematic reviews focused on Alzheimer's disease prevention and 20 reviews focused on symptom management. Virtually all of the reviews of symptom management conflated patients with Alzheimer's disease and patients with other dementias, and this limitation was reflected in the second part of the messaging statement. After deliberating the evidence base, an expert panel achieved consensus on the following statement: "Regular participation in physical activity is associated with a reduced risk of developing Alzheimer's disease. Among older adults with Alzheimer's disease and other dementias, regular physical activity can improve performance of activities of daily living and mobility, and may improve general cognition and balance. " The statement was rated favourably by a sample of older adults and physicians who treat Alzheimer's disease patients in terms of its appropriateness, utility, and clarity. Conclusion Public health and other organizations that promote physical activity, health and well-being to older adults are encouraged to use the evidence-based statement in their programs and resources. Researchers, clinicians, people with Alzheimer's disease and caregivers are encouraged to adopt the messaging statement and the recommendations in the companion informational resource.